Shedding light on the EpCAM: An overview. Issue 8 (9th January 2019) - Yahyazadeh Mashhadi, Seyed Muhammad; Kazemimanesh, Monireh; Arashkia, Arash; Azadmanesh, Kayhan; Meshkat, Zahra; Golichenari, Behrouz; Sahebkar, Amirhosein
Abstract: The epithelial cell adhesion molecule (EpCAM) is a Type I transmembrane superficial glycoprotein antigen that is expressed on the surface of basolateral membrane of multiple epithelial cells with some exceptions such as epidermal keratinocytes, hepatocytes, thymic cortical epithelial cells, squamous stratified epithelial cells, and myoepithelial cells that do not express the molecule. The molecule plays a pivotal role in the structural integrity, adhesion of the epithelial tissues and their interaction with the underlying layers. EpCAM prevents claudin‐7 and claudin‐1 molecules from degradation, thereby, decreasing the number of tight junctions and cellular interconnections, and promoting the cells toward carcinogenic transformation. Moreover, the mutations in the EpCAM gene lead to congenital tufting enteropathy, severe intestinal epithelium homeostasis disorders, and Lynch and Lynch syndrome. Overexpression of EpCAM on stem cells of some cancers and the presence of this molecule on circulating tumor cells (CTCs) makes it a promising candidate for cancer diagnosis as well as tracing and isolation of CTCs. Abstract : This is a comprehensive review on the diagnostic as well as therapeutic potential of epithelial cell adhesion molecule (EpCAM) in cancer.